Do Asian women have endometrial cancer at a younger age? - Awang, Mokhtar (2014)
The purpose of this study is to examine the epidemiological and clinical characteristics of patients with endometrial adenocarcinoma. This is a retrospective observational study of all cases of endometrial adenocarcinoma managed in Hospital Tengku Ampuan Afzan, from January 2011 until December 2013. During this study period there were 48 cases of endometrial adenocarcinoma. The mean age at diagnosis was 53.5  10.5 year-old (range 30-79). One-fifth of these patients were 45 years and younger. The mean parity was 2.5  2.5. The majority (80%) were obese with a mean BMI of 28.8  5.9. The prevalence of diabetes, hypertension and polycystic ovarian disease were only 30%, 25% and 15% respectively. A significant proportion of women (40%) were in their premenopausal period. The remaining (60%) were in their peri/postmenopausal period. All the patients presented with abnormal uterine bleeding with a mean endometrial thickness of 22.7  13.9mm. Equal numbers of women had office endometrial sampling and hysteroscopy and dilatation and curettage as a primary endometrial assessment. In this study, we found that the positive predictive value (PPV) of office endometrial sampling is 76.0%. The majority of the endometrial carcinoma was of endometriod type (81.3%) and the others were high-grade endometrial carcinoma (4.2%), clear cell adenocarcinoma (4.2%), papillary serous (2.1%) and others (8.3%). The PPV of histological grade obtained via office endometrial sampling for grade 1, grade 2 and grade 3 in comparison to the full histology was 81.8%, 58.8% and 60.0% respectively. However, the differences observed in the PPV for different histological grading did not reach statistical significance (p=0.185). In this study, the majority of patients (66.7%) had stage 1 disease followed by stage 3 (23.0%) at diagnosis. Small percentages of women had stage 2 and stage 4 disease at diagnosis i.e. 6.3% and 4.2% respectively. The majority of patients, 58.3% required further adjuvant treatment while the remaining 41.7% did not need further treatment. The mean age of diagnosis of endometrial cancer in our studied population is about ten years younger compared to Western populations. The percentage of Asian women 45 years and younger diagnosed with endometrial carcinoma was alarmingly high i.e. 4 fold higher compared to Caucasian women. Thus we recommend a lower age threshold for proper evaluation of Asian women presenting with abnormal uterine bleeding i.e. 35 years instead of 45 years as recommended by most cancer centres in the west.